2009
DOI: 10.1002/jcla.20307
|View full text |Cite
|
Sign up to set email alerts
|

Checklist for optimization and validation of real‐time PCR assays

Abstract: Real-time polymerase chain reaction (PCR) is a frequently used technique in molecular diagnostics. To date, practical guidelines for the complete process of optimization and validation of commercial and in-house developed molecular diagnostic methods are scare. Therefore, we propose a practical guiding principle for the optimization and validation of real-time PCR assays. Based on literature, existing guidelines, and personal experience, we created a checklist that can be used in different steps of the develop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
107
0
8

Year Published

2010
2010
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 159 publications
(121 citation statements)
references
References 68 publications
6
107
0
8
Order By: Relevance
“…Our results confirmed that enteric viruses play an important role in pediatric diarrhea, and further that the most common viral agent associated with gastroenteritis is NoV, followed by RV, HAstrV, HBoV, SaV, HPeV, AdV, and SalV. The prevalence rates of RV, SaV, HPeV, AdV, and HBoV were similar to those reported previously [32, 34-36]. However, the detection rates of 40.5 and 18.87% for NoV and HAstrV, respectively, in this study were higher than those reported previously in Italy [37-39] but similar to those in the recent study of Rovida et al [40].…”
Section: Discussionsupporting
confidence: 91%
“…Our results confirmed that enteric viruses play an important role in pediatric diarrhea, and further that the most common viral agent associated with gastroenteritis is NoV, followed by RV, HAstrV, HBoV, SaV, HPeV, AdV, and SalV. The prevalence rates of RV, SaV, HPeV, AdV, and HBoV were similar to those reported previously [32, 34-36]. However, the detection rates of 40.5 and 18.87% for NoV and HAstrV, respectively, in this study were higher than those reported previously in Italy [37-39] but similar to those in the recent study of Rovida et al [40].…”
Section: Discussionsupporting
confidence: 91%
“…The development of a "in-house" Real Time RT-PCR assay, available for diagnostic routine, requires an analogous process applied to marked and approved commercial kit for diagnostic use (4,8). This is realized by the standardization and optimization of the amplification protocol; however, also RNA extraction and reverse transcription protocols should be considered in the method assessment.…”
Section: Discussionmentioning
confidence: 99%
“…All assays were carried out on a Stratagene Mx3005P thermal cycler. Assay characteristics, including reaction efficiency, dynamic range, intraand interassay variability, and limit of detection, were determined as described previously (7). The sensitivity of the assay for detecting genomic DNA from diverse A. baumannii strains was determined using purified genomic DNA (QIAamp DNA minikit; Qiagen) from 20 clonally distinct clinical isolates, as determined by pulsed-field gel electrophoresis or repetitive element PCR (REP-PCR).…”
mentioning
confidence: 99%